2016
DOI: 10.1001/jamapediatrics.2016.1446
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease at 50 Years

Abstract: CONCLUSIONS AND RELEVANCE Kawasaki disease is a hybrid condition at the junction of infectious diseases, immunology, rheumatology, and cardiology. Rather than being left an orphan disease, KD is bringing disciplines together to identify its genetic, pathophysiological, and hemodynamic features. In turn, this work promises to shed light on many other inflammatory conditions as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 70 publications
(98 reference statements)
1
35
1
Order By: Relevance
“…Kawasaki disease (KD) is an acute idiopathic systemic vasculitis characterized by fever, bilateral non-exudative conjunctivitis, mucositis, cervical lymphadenopathy, polymorphous eruption, and changes in the extremities [ 1 , 2 ]. Most patients with KD are younger than 5 years old, although the disease can also occur in adolescents [ 2 ]. KD is the leading cause of pediatric-acquired heart disease in North America, Europe, and Japan [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kawasaki disease (KD) is an acute idiopathic systemic vasculitis characterized by fever, bilateral non-exudative conjunctivitis, mucositis, cervical lymphadenopathy, polymorphous eruption, and changes in the extremities [ 1 , 2 ]. Most patients with KD are younger than 5 years old, although the disease can also occur in adolescents [ 2 ]. KD is the leading cause of pediatric-acquired heart disease in North America, Europe, and Japan [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with KD are younger than 5 years old, although the disease can also occur in adolescents [ 2 ]. KD is the leading cause of pediatric-acquired heart disease in North America, Europe, and Japan [ 2 , 3 ]. It results in coronary artery aneurysms in 20–25% of untreated cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KD is the leading cause of acquired heart disease in children, given its coronary artery complications [9,10], and there is still no effective therapy to prevent or treat the occurrence of coronary artery damage due to the limited information. It has been shown that coronary artery endothelial dysfunction plays an important role in the development of coronary artery damage under KD condition [11,6].…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease (KD) is a hybrid condition at the junction of infectious diseases, immunology, rheumatology, and cardiology. 1 KD is a systemic vasculitis of unknown etiology predominately affecting medium-sized vessels such as the coronary arteries, which mainly affects infants and children 2 . The disease itself may be the characteristic manifestation of a common pathway of immune-mediated vascular inflammation in genetically susceptible hosts 3 .…”
Section: Introductionmentioning
confidence: 99%